TRANSITIVITY ON OPRAH WINFREY’S SPEECH AT GENERAL LECTURE OF UNIVERSITIES GRADUATIONS - Marbun Yefta Vianus (Journal of Maritime and Education (JME), 2022)
This descriptive qualitative research deals with the types of Transitivity Process on Oprah Winfrey’s Speech. The objectives of this study are to find out: the types of Transitivity Process occurred in Oprah Winfrey’s speech; the dominant type of process found in Book of Titus and; the reasons of why one process is dominantly used in Book of Titus. The data of this study were Oprah Winfrey’s speeches which are delivered to universities graduation of five universities such as University of Duke, Harvard, Howard, Standford, and Wellesly. There were 2502 clauses of the total clauses in her five speeches. The findings showed that there were six types of process occurred, Material Process (28.25%), Mental Process (20.94%), Behavioral Process (7.43%), Relational Process (33.13%), Verbal Process (8.79%), and Existential Process (1.43%). Relational Process is the process which is dominantly used in Oprah Winfrey’s speech. It could be implied that the clauses in Oprah Winfrey’s speech mostly related to giving some encouragements to the universities graduations through personal potential and through experience of moving forward in facing the hardship of life.